Assessment of crystallographic and electronic phase stability of shock wave loaded cubic cerium oxide nanoparticles. Issue 2 (15th January 2022) - Sivakumar, A.; Ramya, S.; Sahaya Jude Dhas, S.; Almansour, Abdulrahman I.; Kumar, Raju Suresh; Arumugam, Natarajan; Murugesan, Magesh; Martin Britto Dhas, S.A.
Abstract: Rapid progress has been documented during the last couple of years in understanding the crystallographic structural features of a few functional materials that have been achieved under dynamic shock wave loaded conditions. In this context, we report the crystallographic and electronic phase stability of shock wave loaded Cerium oxide nano-crystalline (CeO2 NPs) material and the results have been evaluated by X-ray diffraction (XRD), Raman spectroscopy and ultra-violet diffuse reflectance spectroscopy (UV-DRS). XRD and Raman spectroscopic results show that the title material doesn't undergo any crystallographic phase transitions. UV-DRS spectral results demonstrate that the Ce 4+ ionic state is not affected by the impact of shock waves. The obtained FE-SEM micrographs provide the substantiation for the stability of the sample. Based on the observed results, the title material can be suggested for the making of medical glassware, spaceship windows and technological applications of coating.